Analyzing The Relationship Between Sustainable Development Indicators And Renewable Energy Consumption - Rania Hamed El Sayed Youssef Rashed (2022)
(3edN`U GdQSGdI(B: (3GdGfJbGd Edi GdGYJeGO Ydi eUGOQ GdWGbI GdeJLOOI jeKd JMOkjG cHjkQG ddHdOGf GdeJbOeI hGdfGejI dPG JgOa GdOQGSI Edi GdJMbb ef GdYdGbI Hjf eDTQGJ GdJfejI GdeSJOGeI hGSJgdGc GdWGbI GdeJLOOI HGSJNOGe eLehYGJ HjGfGJ eJcGedI d` (B255 (3eDTkQG JYHQ Yf CgOGa GdJfejI GdeSJOGeI ef (B137 (3OhdI eJbOeI hfGejI(B. (3GdfehPL GdQjGVj GdeSJNOe jJchf ef GNJHGQ JMdjd GdechfGJ GdQFjSjI, Ke GNJHGQ GdGfMOGQ GdNWj GdeJYOO hGdPj jeKd GdYdGbI GdYOOjI Hjf eLehYI ef eDTQGJ GdJfejI GdeSJOGeI hGSJgdGc GdWGbI GdeJLOOI(B. (3fJGFL GdJMdjd GdEMUGFj GTJedJ Ydi (B(1) (3hLhO GQJHGW YcSj Hjf eDTQ GdJfejI GdeSJOGeI GdPj jYHQ Yf GdYGed Gdegjef GdPj jeKd GdHjGfGJ GdeLeYI hGSJgdGc GdWGbI GdeJLOOI, (B(2) (3GSJfJGL eLehYI ef eDTQGJ GdJfejI GdeSJOGeI ceMOOGJ dGSJgdGc GdWGbI GdeJLOOI(B. (3JaSQ GdfJGFL GdJMhd GdSQjY ddHdOGf GdefNaVI eDTQ GdJfejI GdeSJOGeI fMh JcfhdhLjG GdWGbI GdeJLOOI ef NdGd EOQGc GdOhQ GdaYGd dGSJNOGe GdWGbI GdeJLOOI cMd eMdj(B. (3HGdEVGaI Edi Pdc, JXgQ GdfJGFL CgejI eDTQGJ GdJfejI GdeSJOGeI GdeSJfJLI ddeNWWjf hUfGY GdbQGQ aj RjGOI GSJgdGc GdWGbI GdeJLOOI dEMQGR GdGfJbGd fMh GdWGbI GdeJLOOI HeG jJeGTi eY JMbjb GdJfejI GdeSJOGeI(B.s
Thesis (Ph.D)-Cairo University,2022.
Bibliography: p. 81-87.
Keywords: renewable energy; Sustainable development Indicators